Análisis y evaluación económica y financiera de las cooperativas de ahorro y crédito del segmento 3 de la ciudad de Loja, estudio de caso en la cooperativa de ahorro y crédito Cristo Rey, periodo 2019-2020 - Lozano Ojeda, Mónica Janina (2022)
Credit Unions are really important within the financial sector of Ecuador, since they stimulate financial intermediation through the capture of surpluses from natural and legal people, channeling them into credits from other companies that require financing for the normal development of its operations, according to the scope of its competence. In the investigation, the diagnosis of the economic and financial structure of the savings and credit cooperatives of segment 3 and about the study of the "Cristo Rey" credit union was developed, through vertical and horizontal analysis and financial indicators. Established by the SEPS, included in the 2019-2020 study period, the financial report was prepared with the main conclusions and recommendations of the study. The research was descriptive - analytical with a quantitative approach, whose population that corresponds to three existing institutions in Loja city, allowing to provide alternative solutions that help managers and administrators to make the respective decisions that help manage operational management of financial entities. The results determined that the credit portfolio of the credit unions of segment 3, had a greater participation in the year 2019 with 80,28% compared to 72,01% in 2020, demonstrating that the entity despite the negative effects of the health crisis managed to place a significant percentage of credits that allowed him to cover his financial costs almost in full; the item obligations with the public with a decrease of 2.06% originated by the withdrawal of savings from partners and by restricted deposits that are reserve savings, a situation that generates greater responsibility for financial entities, results that show that they are normally covering the obligations they have; Finally, in the capital stock there is a slight decrease of 1,26%, caused by the withdrawal of some partners due to the uncertainty caused by the health crisis, being an unfavorable point that is currently being solved through quality financial services.